Biosynthesis pathways of ginkgolides - Zeng, Zihan; Zhu, Jianhua; Chen, Lili; Wen, Wei; Yu, Rongming (Pharmacognosy Reviews, 2013)
The ginkgolides, acting as anti‑platelet‑activating factors, have been studied for many years. The biosynthetic pathway of ginkgolides is still far away from unveiling at the level of molecular genetics and biochemistry. There are at least 11 kinds of enzymes having been cloned from Ginkgo biloba L., which catalyze the formation of ginkgolides via a series of reactions. Some researchers have indicated that the addition of precursors and elicitors can influence the accumulation of ginkgolides in the suspension cell cultures of G. biloba. There are also other factors that can influence the production of ginkgolides. This review focuses on the aforementioned aspects to discuss the biosynthetic pathways of the ginkgolides.
Keywords: Biosynthetic pathways; cell culture; enzymes; genes; Ginkgo biloba; ginkgolides